PROPOSTA DE SISTEMATIZAÇÃO DO PROCESSO DA GARANTIA METROLÓGICA PARA INSTRUMENTOS DE MEDIÇÃO - Silva, Luzia Gomes (2007)
The knowledge on new researches returned to the legal metrology is a tool that will allow increasing the trust in the accomplished measurements. This research approaches the main concepts returned to the use of the knowledge in the organizations. It explains the general aspects of the metrology, it current context as for the implantation of the metrologic control of the measurement instruments and it presents the concept of metrologic assurance. The work has as objective shows the importance of the process of metrologic assurance for the development of the metrologic control of the measurement instruments and to present an improvement proposal. It was still made a discussion about acquisition of the knowledge no codified in the metrologic assurance. The results demonstrate the need of larger investment in the managers' of new researches training on measurement instruments, as the metrologic assurance for such instruments